(untitled) (Historia, 2021)
This work is not a conventional autobiography or memoir. Even after more than 500 pages, General Magnus Malan’s private life remains a closed book. His childhood, marriage and fatherhood appear almost incidental to what is essentially the story of a professional career. It reads like an institutional history of the South African Defence Force (SADF), wherein the subject inserts his own life story. As the author himself puts it, "42 years of my life were inextricably entwined with the Defence Force" (p 432). Malan’s very identity is bound up in the SADF; it is the SADF that defines who Malan is and gives his life story meaning. This much is implied in the book’s Afrikaans title: "My lewe saam met die SA Weermag". The English title, however, does not suggest quite the same degree of intimacy. Still, this close association means that Malan embodied the SADF’s ethos during the 1970s and 1980s, and that the technocrat turned securocrat left an indelible imprint on the institution.